A lubricant composition resistant to high temperature oxidation and its preparation method and application

CN123004469APending Publication Date: 2026-10-30HAFERD PETROLEUM ENERGY GUANGDONG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611295010.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

该技术方案虽然具有良好的导热性能,然而却没有验证在高温下的抗氧化性和润滑性能

Benefits of technology

1、本发明通过双端乙烯基含氟硅油和3-羟基-1-金刚烷基甲基丙烯酸酯之间的加成反应聚合包覆在纳米氮化硼表面制备得到了改性纳米氮化硼,不仅有效提高纳米氮化硼的分散均匀性,充分发挥纳米氮化硼的导热、抗磨作用,而且有效提高润滑剂组合物的抗高温氧化性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The application belongs to the technical field of lubricants, and particularly relates to a high-temperature oxidation-resistant lubricant composition and a preparation method and application thereof. The high-temperature oxidation-resistant lubricant composition comprises the following raw materials in percentage by mass: a viscosity index improver 3-7%, a dispersant 0.5-4%, an antioxidant 0.5-2%, an extreme pressure and anti-wear agent 0.5-1.5%, a metal deactivator 0.3-0.8%, modified nanometer boron nitride 0.05-0.3%, a pour point depressant 0.05-0.3%, a defoaming agent 0.02-0.05%, and a base oil supplementing the rest to 100%. The modifier of the modified nanometer boron nitride comprises a double-end vinyl fluorine-containing silicone oil and 3-hydroxy-1-adamantyl methacrylate. The lubricant composition provided by the application has excellent high-temperature oxidation resistance, insulation, corrosion resistance and wear resistance, and can be applied to new energy electric vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lubricant technology, specifically relating to a high-temperature oxidation resistant lubricant composition, its preparation method, and its application. Background Technology

[0002] With the green transformation of the global automotive industry and the rise of new energy vehicles, especially electric vehicles, new challenges and demands have been placed on the lubricant industry.

[0003] Electric vehicles typically employ an integrated electric drive unit that combines a motor, reducer, and inverter. Therefore, electric drive transmission fluid faces multiple challenges: First, the electric drive system can reach speeds exceeding 16,000 rpm, and the motor generates enormous heat during high-speed operation, with stator temperatures reaching as high as 170°C. Therefore, the lubricant must not only possess excellent anti-wear and lubrication properties but also excellent resistance to high-temperature oxidation. Second, the lubricant in the electric vehicle drive system will be in prolonged, high-temperature contact with large areas of copper-containing electrical components. Therefore, the lubricant needs to possess good insulation and corrosion resistance.

[0004] The applicant previously developed an antioxidant lubricating oil composition, with publication number CN 121518202 A. This technical solution uses graphene as a thermally conductive material, and the resulting lubricating oil composition has excellent antioxidant properties and improved thermal conductivity. However, the graphene in this technical solution is conductive, so it can only be applied to dual-fuel engines and cannot be applied to electric vehicles.

[0005] Chinese Patent CN119307307A discloses a high-temperature resistant and corrosion-resistant lubricating oil for electric vehicle transmissions. This lubricating oil is made from the following raw materials in weight percentages: 80-120 parts base oil, 5-10 parts modified silicone oil, 1-5 parts dispersant, 0.5-3 parts extreme pressure anti-wear agent, 0.5-3 parts antioxidant, 0.05-0.5 parts metal deactivator, and 0.05-0.5 parts defoamer. This technical solution prepares the lubricating oil by adding appropriate proportions of viscosity index improver, dispersant, extreme pressure anti-wear agent, antioxidant, metal deactivator, and defoamer to the base oil. This lubricating oil has excellent lubrication and cooling properties, as well as good high-temperature resistance and corrosion resistance, enabling it to maintain good lubrication effects even at high temperatures, reducing corrosion of metal parts, effectively extending the service life of the lubricating oil, and meeting the requirements for electric vehicle transmission lubricating oil. While this technical solution has good thermal conductivity, its oxidation resistance and lubrication performance at high temperatures have not been verified. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a high-temperature oxidation resistant lubricant composition, its preparation method, and its application. The lubricant composition provided by this invention possesses excellent high-temperature oxidation resistance, insulation, corrosion resistance, and wear resistance.

[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a high-temperature oxidation resistant lubricant composition, comprising, by weight percentage: 3-7% viscosity index improver, 0.5-4% dispersant, 0.5-2% antioxidant, 0.5-1.5% extreme pressure anti-wear agent, 0.3-0.8% metal deactivator, 0.05-0.3% modified nano boron nitride, 0.05-0.3% pour point depressant, 0.02-0.05% defoamer, and base oil to make up the balance to 100%; The modifiers for the modified nano boron nitride include dual-terminated vinyl fluorinated silicone oil and 3-hydroxy-1-adamantyl methacrylate.

[0008] Preferably, the volume resistivity of the lubricant composition is ≥480 MΩ·m (25°C); the copper strip corrosion level is ≥1a (150°C, 192h).

[0009] Preferably, the viscosity change rate of the lubricant composition is <1.5% (170°C, 192h); and the acid value change is <0.3 (calculated as KOH, 170°C, 192h).

[0010] Preferably, the viscosity index improver is selected from one or more of polymethacrylate, polyisobutylene, ethylene-propylene copolymer and polyisoprene.

[0011] Preferably, the dispersant is selected from one or more of polyisobutylene succinimide and boronized polyisobutylene succinimide.

[0012] Preferably, the antioxidant is selected from one or more of alkylated diphenylamine, N-phenyl-α-naphthylamine, and phenolic esters.

[0013] Preferably, the extreme pressure anti-wear agent is selected from one or more of triphenyl thiophosphate, zinc dialkyl dithiophosphate, and tributyl phosphate.

[0014] Preferably, the metal deactivator is prepared by hydrosilylation reaction of terminal hydrofluorosilicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole.

[0015] Preferably, the metal deactivator is prepared as follows: hydrofluoric acid-terminated silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole are mixed, heated under nitrogen protection, and chloroplatinic acid catalyst is added. The mixture is then kept at the temperature and stirred to obtain the final product.

[0016] Lubricants prepared using conventional metal deactivators exhibit decreased adsorption rates and reduced stability of the protective film at high temperatures, leading to poorer corrosion resistance. To address this issue, this invention prepares a metal deactivator containing both benzotriazole groups and fluorosilicone segments via a hydrosilylation reaction of hydrofluorosilicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole. The fluorosilicone segments in the hydrofluorosilicone oil not only enhance the high-temperature resistance of the metal deactivator but also provide a physical barrier effect during the chemical adsorption of the benzotriazole groups onto the metal surface to form stable coordination bonds. This further repels moisture, acidic oxides, and corrosive ions, resulting in excellent corrosion resistance in the lubricant composition.

[0017] Preferably, the structure of the end-containing hydrofluoric silicone oil is as follows: , n=5-20.

[0018] Preferably, the molar ratio of the hydrofluoric silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole is 1:2-2.4.

[0019] Preferably, the chloroplatinic acid catalyst is added in the form of a chloroplatinic acid isopropanol solution with a concentration of 0.005-0.02 g / mL.

[0020] Preferably, the amount of chloroplatinic acid catalyst added is 10-30 ppm of the total mass of hydrofluoric acid-terminated silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole.

[0021] Preferably, the temperature after heating is 70-90℃, and the time for heat preservation and stirring reaction is 5-8 hours.

[0022] Preferably, the modified boron nitride nanoparticles are prepared as follows: boron nitride nanoparticles are dispersed in a solvent, and double-ended vinyl fluorinated silicone oil, 3-hydroxy-1-adamantyl methacrylate and an initiator are added. The mixture is heated and stirred under nitrogen protection. After the reaction is completed, the solvent is removed by rotary evaporation to obtain the product.

[0023] This invention prepares modified boron nitride nanoparticles by polymerizing a mixture of divinyl-terminated fluorinated silicone oil and 3-hydroxy-1-adamantyl methacrylate onto the surface of boron nitride nanoparticles. This not only effectively improves the dispersion uniformity of the boron nitride nanoparticles and fully utilizes their thermal conductivity and anti-wear properties, but also effectively enhances the high-temperature oxidation resistance of the lubricant composition. This is likely due to the excellent thermal stability of the polymer layer formed by the divinyl-terminated fluorinated silicone oil and 3-hydroxy-1-adamantyl methacrylate, and the high rigidity and strong bond energy of the adamantane structure, which effectively inhibits the oxidation reaction of the lubricant composition at high temperatures. Simultaneously, the fluorinated silicone oil portion imparts low surface energy and high chemical inertness to the lubricant composition, reducing contact between the metal surface and oxygen, moisture, and acidic products, thereby delaying oxidative deterioration. Furthermore, this coating layer can form a protective transfer film during friction, isolating direct metal contact and reducing wear, thus further improving anti-wear performance.

[0024] Preferably, the particle size of the nano-boron nitride is 50-100 nm.

[0025] Preferably, the solvent is N,N-dimethylformamide.

[0026] Preferably, the initiator is azobisisobutyronitrile.

[0027] Preferably, the structure of the double-ended vinyl fluorinated silicone oil is as follows: , n=3-20.

[0028] Preferably, the ratio of the nano-boron nitride, solvent, dual-terminated vinyl fluorinated silicone oil, 3-hydroxy-1-adamantyl methacrylate, and initiator is 10:30-50:1-3:1-2:0.015-0.04.

[0029] Preferably, the heating and stirring reaction is carried out at a temperature of 60-70°C for 3-5 hours.

[0030] Preferably, the pour point depressant is polymethacrylate.

[0031] Preferably, the defoamer is selected from one or more of polyether-type defoamers, silicone-type defoamers, and polyether-modified silicone-type defoamers.

[0032] Preferably, the base oil is selected from one or more of Group II hydrotreated base oils, Group III hydrotreated base oils, and polyalphaolefins.

[0033] Secondly, the present invention provides a method for preparing a high-temperature oxidation resistant lubricant composition, comprising the following steps: adding an extreme pressure anti-wear agent, modified nano boron nitride, a dispersant, an antioxidant, a metal deactivator, a viscosity index improver, a pour point depressant, and an antifoamer to a base oil and mixing them evenly to obtain the lubricant composition.

[0034] Thirdly, the present invention provides an application of a high-temperature oxidation resistant lubricant composition in new energy electric vehicles.

[0035] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. The present invention prepares modified boron nitride nanoparticles by polymerizing the addition reaction between dual-terminated vinyl fluorinated silicone oil and 3-hydroxy-1-adamantyl methacrylate onto the surface of boron nitride nanoparticles. This not only effectively improves the dispersion uniformity of boron nitride nanoparticles and fully utilizes the thermal conductivity and anti-wear properties of boron nitride nanoparticles, but also effectively improves the high-temperature oxidation resistance of the lubricant composition.

[0036] 2. This invention prepares a metal deactivator containing both benzotriazole groups and fluorosilicone segments via a hydrosilylation reaction of hydrofluoric acid-terminated silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole. The fluorosilicone segments in the hydrofluoric acid-terminated silicone oil not only improve the high-temperature resistance of the metal deactivator, but also provide a physical barrier effect while the benzotriazole groups chemically adsorb onto the metal surface to form stable coordination bonds, further repelling moisture, acidic oxides, and corrosive ions, thus giving the lubricant composition excellent corrosion resistance. Detailed Implementation

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] Unless otherwise specified in the examples and comparative examples, the conditions were performed under standard conditions or conditions recommended by the manufacturer. All reagents and instruments used were commercially available products unless otherwise specified.

[0039] Example 1 A high-temperature oxidation resistant lubricant composition, by weight percentage, comprises the following raw materials: 3% viscosity index improver, 4% dispersant, 0.8% antioxidant, 0.8% extreme pressure anti-wear agent, 0.3% metal deactivator, 0.3% modified nano boron nitride, 0.3% pour point depressant, 0.02% defoamer, and base oil to make up to 100%.

[0040] The viscosity index improver is polymethyl methacrylate, manufactured by Evonik Industries, brand name: VISCOPLEX. ® 8-800.

[0041] The dispersant is boronized polyisobutylene succinimide, manufactured by Jinzhou Haorunda Additives Co., Ltd., brand name: HRD1154B.

[0042] The antioxidant is selected from alkylated diphenylamine, manufactured by BASF, brand name: IRGANOX. ® L67.

[0043] The extreme pressure anti-wear agent is triphenyl thiophosphate, manufactured by Jinzhou Chenghua New Materials Co., Ltd., and its brand name is T-309.

[0044] The preparation method of the metal deactivator is as follows: accurately weigh the hydrofluoric silicone oil (Mn=1382) and mix it with 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole. Under nitrogen protection, heat the mixture to 80°C, add chloroplatinic acid catalyst, and stir the mixture for 6 hours to obtain the final product.

[0045] The structural formula of the end-containing hydrofluoric silicone oil is as follows: .

[0046] The molar ratio of the hydrofluoric silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole is 1:2.

[0047] The chloroplatinic acid catalyst was added in the form of a chloroplatinic acid isopropanol solution with a concentration of 0.01 g / mL.

[0048] The amount of chloroplatinic acid catalyst added is 30 ppm of the total mass of hydrofluoric silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole.

[0049] The modified boron nitride nanoparticles are prepared as follows: boron nitride nanoparticles are dispersed in a solvent, and double-terminated vinyl fluorinated silicone oil (Mn=2000), 3-hydroxy-1-adamantyl methacrylate and an initiator are added. Under nitrogen protection, the mixture is stirred and reacted at 65°C for 4 hours. After the reaction is completed, the solvent is removed by rotary evaporation to obtain the product.

[0050] The boron nitride nanoparticles have a particle size of 50 nm.

[0051] The solvent is N,N-dimethylformamide.

[0052] The initiator is azobisisobutyronitrile.

[0053] The structural formula of the double-ended vinyl fluorinated silicone oil is as follows: .

[0054] The composition of the nano-boron nitride, solvent, dual-terminated vinyl fluorinated silicone oil, 3-hydroxy-1-adamantyl methacrylate, and initiator is 10:40:2:1:0.03.

[0055] The pour point depressant is polymethyl methacrylate, manufactured by Jinzhou Chenghua New Materials Co., Ltd., brand name: T602.

[0056] The defoamer is a polyether-type defoamer, manufactured by Dongguan Guozhong New Materials Research Institute Co., Ltd., with the brand name DU-1650.

[0057] The base oil is a polyalphaolefin (PAO4) and PAO6 in a mass ratio of 2:1, manufactured by Shanghai Daopu Chemical Co., Ltd.

[0058] The preparation method of the above-mentioned high-temperature oxidation resistant lubricant composition includes the following steps: adding extreme pressure anti-wear agent, modified nano boron nitride, dispersant, antioxidant, metal deactivator, viscosity index improver, pour point depressant and defoamer to base oil and mixing evenly to obtain the product.

[0059] Example 2 The only difference from Example 1 is that the high-temperature oxidation resistant lubricant composition, by mass percentage, includes the following raw materials: viscosity index improver 5%, dispersant 3%, antioxidant 1%, extreme pressure anti-wear agent 1%, metal deactivator 0.5%, modified nano boron nitride 0.2%, pour point depressant 0.1%, defoamer 0.03%, and base oil to make up to 100%; all other components are the same.

[0060] Example 3 The only difference from Example 1 is that the high-temperature oxidation resistant lubricant composition, by mass percentage, includes the following raw materials: viscosity index improver 7%, dispersant 2%, antioxidant 1.5%, extreme pressure anti-wear agent 1.5%, metal deactivator 0.8%, modified nano boron nitride 0.1%, pour point depressant 0.1%, defoamer 0.05%, and base oil to make up the balance to 100%; all other components are the same.

[0061] Comparative Example 1 The only difference from Example 2 is that the double-ended vinyl fluorinated silicone oil is replaced with an equal mass of double-ended vinyl silicone oil (Mn=2000), with the following structural formula: The rest are the same.

[0062] Comparative Example 2 The only difference from Example 2 is that the dual-terminated vinyl fluorosilicone oil is replaced with an equal mass of 2,4,6-trivinylcycloboroxane; all other aspects are the same.

[0063] Comparative Example 3 The only difference from Example 2 is that 3-hydroxy-1-adamantyl methacrylate is replaced with an equal mass of 2,4,6-trivinylcycloboroxane; all other aspects are the same.

[0064] Comparative Example 4 The only difference from Example 2 is that 3-hydroxy-1-adamantyl methacrylate is replaced with an equal mass of diethyl vinylphosphonate; all other aspects are the same.

[0065] Comparative Example 5 The only difference from Example 2 is that the modified boron nanonitride is replaced with boron nanonitride; everything else is the same.

[0066] Comparative Example 6 The only difference from Example 2 is that the hydrofluoric acid-containing silicone oil at the end is replaced with an equal mass of hydrofluoric acid-containing silicone oil at the end (Mn=1025), with the following structural formula: The rest are the same.

[0067] Comparative Example 7 The only difference from Example 2 is that the metal deactivator is methylbenzotriazole; everything else is the same.

[0068] Comparative Example 8 The only difference from Example 2 is that the metal deactivator is a condensate of N,N-dialkylaminomethylenetriazole and thiadiazole tert-dodecyl mercaptan in a mass ratio of 1:2; all other aspects are the same.

[0069] Performance testing: The lubricant compositions prepared in the above examples and comparative examples were subjected to the following performance tests.

[0070] Table 1

[0071] Table 2

[0072] Data Analysis: As can be seen from Tables 1 and 2, the lubricant composition prepared by the present invention has excellent high-temperature oxidation resistance, corrosion resistance, insulation and wear resistance. Comparative Example 1 replaced the double-ended vinyl fluorinated silicone oil with an equal mass of double-ended vinyl silicone oil; Comparative Example 2 replaced the double-ended vinyl fluorinated silicone oil with an equal mass of 2,4,6-trivinylcycloboroxane; Comparative Example 3 replaced 3-hydroxy-1-adamantyl methacrylate with an equal mass of 2,4,6-trivinylcycloboroxane; Comparative Example 4 replaced 3-hydroxy-1-adamantyl methacrylate with an equal mass of diethyl vinylphosphonate; The viscosity change rate, acid value change, and wear scar diameter of the lubricant compositions obtained in Comparative Examples 1-4 were significantly increased; Comparative Example 5 did not modify the nano-boron nitride, and the viscosity change rate, acid value change, and wear scar diameter of the obtained lubricant composition were significantly increased, while the copper strip corrosion level decreased; Comparative Examples 1-5 show that modifying nano-boron nitride with double-ended vinyl fluorinated silicone oil and 3-hydroxy-1-adamantyl methacrylate can not only significantly improve the high-temperature oxidation resistance and anti-wear performance of the lubricant composition, but also improve its corrosion resistance.

[0073] Comparative Example 6 replaced the end-containing hydrofluoric silicone oil with an equal mass of end-containing hydrogen silicone oil; the metal deactivators in Comparative Examples 7 and 8 were conventional metal deactivators in the art. The copper sheet corrosion level of the lubricant compositions obtained in Comparative Examples 6-8 was significantly reduced. Comparative Examples 6-8 show that the self-made metal deactivator of the present invention can significantly improve the corrosion resistance of the lubricant composition.

[0074] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A lubricant composition resistant to high-temperature oxidation, characterized in that, By weight percentage, it includes the following raw materials: Viscosity index improver 3-7%, dispersant 0.5-4%, antioxidant 0.5-2%, extreme pressure anti-wear agent 0.5-1.5%, metal deactivator 0.3-0.8%, modified nano boron nitride 0.05-0.3%, pour point depressant 0.05-0.3%, defoamer 0.02-0.05%, base oil to make up to 100%; The modifiers for the modified nano boron nitride include dual-terminated vinyl fluorinated silicone oil and 3-hydroxy-1-adamantyl methacrylate.

2. The high-temperature oxidation resistant lubricant composition according to claim 1, characterized in that, The viscosity change rate of the lubricant composition is <1.5% at 170°C for 192 hours; the acid value change is <0.3 (based on KOH) at 170°C for 192 hours.

3. The high-temperature oxidation resistant lubricant composition according to claim 1 or 2, characterized in that, The volume resistivity of the lubricant composition is ≥480 MΩ·m at 25℃; the copper sheet corrosion level is ≥1a at 150℃ for 192 hours.

4. The high-temperature oxidation resistant lubricant composition according to claim 1, characterized in that, The metal deactivator is prepared by hydrosilylation reaction of terminal hydrofluoric silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole.

5. The high-temperature oxidation resistant lubricant composition according to claim 4, characterized in that, The metal deactivator is prepared as follows: Hydrofluoric silicone oil and 2-(2'-hydroxy-3'-methallyl-5'-methylphenyl)benzotriazole are mixed, heated under nitrogen protection, and chloroplatinic acid catalyst is added. The mixture is then stirred and kept at the temperature to obtain the final product.

6. The high-temperature oxidation resistant lubricant composition according to claim 5, characterized in that, The structural formula of the end-containing hydrofluoric silicone oil is as follows: ,n=5-20。 7. The high-temperature oxidation resistant lubricant composition according to claim 1, characterized in that, The modified boron nitride nanoparticles are prepared as follows: boron nitride nanoparticles are dispersed in a solvent, and double-terminated vinyl fluorinated silicone oil, 3-hydroxy-1-adamantyl methacrylate and an initiator are added. The mixture is heated and stirred under nitrogen protection. After the reaction is completed, the solvent is removed by rotary evaporation to obtain the product.

8. The high-temperature oxidation resistant lubricant composition according to claim 7, characterized in that, The structural formula of the double-ended vinyl fluorinated silicone oil is as follows: ,n=3-20。 9. A method for preparing the high-temperature oxidation-resistant lubricant composition according to any one of claims 1-8, characterized in that, Includes the following steps: The extreme pressure anti-wear agent, modified nano boron nitride, dispersant, antioxidant, metal deactivator, viscosity index improver, pour point depressant and defoamer are added to the base oil and mixed evenly to obtain the product.

10. The application of the high-temperature oxidation resistant lubricant composition according to any one of claims 1-8 in new energy electric vehicles.

Citation Information

Patent Citations

  • High-temperature-resistant anti-corrosion lubricating oil for transmission of electric vehicle

    CN119307307A

  • Anti-oxidation lubricating oil composition, preparation method and application of anti-oxidation lubricating oil composition to dual-fuel engine

    CN121518202A